Mengukur Kinerja Keuangan PT BNI (Persero) Tbk dengan Menggunakan Rasio Keuangan - Irna Roseniati; Yenny Ernitawati; Roni; Muhammad Badrun Zaman; Titi Rahmawati (Universitas Muhadi Setiabudi, 2019)
Financial performance is an illustration of a company's success that can be used as a basis for making decisions by analyzing financial reports using profitability ratios (Return on Assets, Return on Equity and Net Profit Margin), solvency ratios (Debt to Assets and Debt to Equity) and growth ratios ( net profit growth, growth in share earnings and growth in total assets) which has the aim of knowing and explaining an overview of financial performance at PT BNI Persero) Tbk in each period. The object used comes from PT BNI (Persero) Tbk with population and samples taken from financial statements, in the form of balance sheets and income statements for 5 periods, namely 2017 to 2019. The type of approach used is a deductive approach with secondary data with a horizontal analysis method carried out by comparing financial reports use ratios to determine the company's financial performance. The results of the analysis of the financial performance of PT. BNI (Persero) Tbk is quite good, even though there were many percentage reductions in the profitability ratio and growth ratio in 2018, the company was able to increase the percentage again the following year.